2019
DOI: 10.1029/2018jb016823
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Law for Earthquake Production Based on Rate‐and‐State Friction: Theory and Application of Interacting Sources

Abstract: The constitutive relationship of Dieterich (1994, https://doi.org/10.1029/93JB02581) for earthquake production has been applied widely to earthquake triggering. The Dieterich theory achieves mathematical simplicity and thus lends itself to practical applications through a number of simplifying assumptions. Perhaps the most suspect and criticized assumption is that seismic sources do not interact. Here I provide an extension of the constitutive framework, using the modified formulation of Heimisson and Segall (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 26 publications
(69 reference statements)
1
20
0
Order By: Relevance
“…This indicates that a population with interactions can be approximated as a population without interactions with the same long‐term average background seismicity rate. In addition, Heimisson () showed that interaction between populations in a spatially heterogeneous stress field do not change the absolute number of events on a regional scale for times tta. This suggests that interactions do not change the absolute number of events, although they may somewhat change their temporal and spatial distribution.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that a population with interactions can be approximated as a population without interactions with the same long‐term average background seismicity rate. In addition, Heimisson () showed that interaction between populations in a spatially heterogeneous stress field do not change the absolute number of events on a regional scale for times tta. This suggests that interactions do not change the absolute number of events, although they may somewhat change their temporal and spatial distribution.…”
Section: Discussionmentioning
confidence: 99%
“…In Groningen, apart from the absence of any (known) tectonic activity, no seismicity was observed for the first 20-25 yr of gas production. This absence of seismicity implies that no fault segments within the Groningen gas field have near-threshold initial stresses at the onset of depletion (Muntendam-Bos & de Waal 2013;Wees et al 2014;Bourne & Oates 2017;Dempsey & Suckale 2017;Candela et al 2018) or the tectonic loading rate is very low, resulting in a very low background seismicity rate (Dieterich 1994;Heimisson 2019). In terms of changes in effective stress, the Mohr-Coulomb circle is far from the failure line, but slowly grows with ongoing pressure depletion (Fig.…”
Section: Gas Production and (Background) Seismicity Ratesmentioning
confidence: 99%
“…This indicates that a population with interactions can be approximated as a population without interactions with the same long term average background seismicity rate. In addition, Heimisson [2019] showed that interaction between populations in a spatially heterogeneous stress field, do not change the absolute number of events on a regional scale for times t t a . This suggests that interactions do not change the absolute number of events, although they may somewhat change their temporal and spatial distribution.…”
Section: Secondary Triggeringmentioning
confidence: 99%
“…However, the population of seismic sources (see Heimisson [2019] for precise definition) may not have been sufficiently stressed prior to the intrusion to produce earthquakes at a constant rate. Indeed, Figure 5 suggests that in most places the background shear to normal stress ratio was fairly small.…”
Section: Time-dependent Estimation Of Dike Pressure and Stressing Hismentioning
confidence: 99%